European Groundshot—addressing Europe's cancer research challenges: a Lancet Oncology Commission - Lawler, Mark; Davies, Lynne; Oberst, Simon; Oliver, Kathy; Eggermont, Alexander; Schmutz, Anna; La Vecchia, Carlo; Allemani, Claudia; Lievens, Yolande; Naredi, Peter; Cufer, Tanja; Aggarwal, Ajay; et al. (The lancet oncology, 2023)
Cancer research is a crucial pillar for countries to deliver more affordable, higher quality, and more equitable cancer care. Patients treated in research-active hospitals have better outcomes than patients who are not treated in these settings. However, cancer in Europe is at a crossroads. Cancer was already a leading cause of premature death before the COVID-19 pandemic, and the disastrous effects of the pandemic on early diagnosis and treatment will probably set back cancer outcomes in Europe by almost a decade. Recognising the pivotal importance of research not just to mitigate the pandemic today, but to build better European cancer services and systems for patients tomorrow, the Lancet Oncology European Groundshot Commission on cancer research brings together a wide range of experts, together with detailed new data on cancer research activity across Europe during the past 12 years. We have deployed this knowledge to help inform Europe's Beating Cancer Plan and the EU Cancer Mission, and to set out an evidence-driven, patient-centred cancer research roadmap for Europe. The high-resolution cancer research data we have generated show current activities, captured through different metrics, including by region, disease burden, research domain, and effect on outcomes. We have also included granular data on research collaboration, gender of researchers, and research funding. The inclusion of granular data has facilitated the identification of areas that are perhaps overemphasised in current cancer research in Europe, while also highlighting domains that are underserved. Our detailed data emphasise the need for more information-driven and data-driven cancer research strategies and planning going forward. A particular focus must be on central and eastern Europe, because our findings emphasise the widening gap in cancer research activity, and capacity and outcomes, compared with the rest of Europe. Citizens and patients, no matter where they are, must benefit from advances in cancer research. This Commission also highlights that the narrow focus on discovery science and biopharmaceutical research in Europe needs to be widened to include such areas as prevention and early diagnosis; treatment modalities such as radiotherapy and surgery; and a larger concentration on developing a research and innovation strategy for the 20 million Europeans living beyond a cancer diagnosis. Our data highlight the important role of comprehensive cancer centres in driving the European cancer research agenda. Crucial to a functioning cancer research strategy and its translation into patient benefit is the need for a greater emphasis on health policy and systems research, including implementation science, so that the innovative technological outputs from cancer research have a clear pathway to delivery. This European cancer research Commission has identified 12 key recommendations within a call to action to reimagine cancer research and its implementation in Europe. We hope this call to action will help to achieve our ambitious 70:35 target: 70% average 10-year survival for all European cancer patients by 2035.